ChemInform Abstract: Achievement of Regioselectivity in Transition Metal‐Catalyzed Direct C—H (Hetero)Arylation Reactions of Heteroarenes with One Heteroatom Through the Use of Removable Protecting/Blocking Substituents or Traceless Directing Groups. Issue 20 (April 2016) - Rossi, Renzo; Lessi, Marco; Manzini, Chiara; Marianetti, Giulia; Bellina, Fabio
Abstract: Review: [175 refs.